Testicular lymphoma: Clinical and imaging features - Pattamapaspong N. (2017)
© 2016 Hong Kong College of Radiologists. Objective: To review the clinical presentation and imaging features of testicular lymphoma. Methods: We retrospectively reviewed the clinical data, and grey-scale and colour Doppler ultrasound features of 11 patients with proven testicular lymphoma between January 2000 and September 2013. The patients were aged 35 to 84 years (mean, 59 years). The diagnosis was established by orchidectomy in eight patients, by compelling evidence including bone marrow and lymph node biopsy in two, and autopsy in one. Results: Of the 11 patients, seven presented with painless scrotal mass(es), three presented with an afebrile painful scrotal mass, and one presented with a febrile painful scrotal mass. Disease was unilateral in nine patients and bilateral in two. Primary testicular lymphoma was diagnosed in six patients and secondary testicular lymphoma in five, of which nine were non-Hodgkin's lymphoma with diffuse large B-cell lymphoma (DLBCL) and two were T-cell lymphoma. Ultrasonography revealed diffuse hypoechoic involvement in seven patients, a solitary hypoechoic mass in two patients, and bilateral multiple hypoechoic masses in two patients. All lesions showed hypervascularity. Enlarged epididymis with hypervascularity was present in two patients mimicking epididymoorchitis. Conclusion: Testicular lymphoma is predominantly DLBCL. Patients may present with painless or painful scrotal mass(es). Lymphoma should be considered in a man older than 50 years who presents with testicular mass regardless of pain with focal or diffuse hypervascular hypoechoic testicular lesion(s) on ultrasound. The associated hypervascular enlarged epididymis does not exclude the diagnosis of testicular lymphoma.